Elliptic Curve Cryptography Based Data Transmission against Blackhole Attack in MANET - Jeenat Sultana; Tasnuva Ahmed (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Mobile nodes roaming around in the hostile environment of mobile adhoc network (MANET) play the role of router as well as terminal. While acting as a router, a node needs to choose a reliable routing protocol. Besides, an encryption algorithm is needed to secure data to be conveyed through the unfriendly atmosphere while acting as a terminal. We have implemented Elliptic Curve Cryptography (ECC) along with Adhoc On Demand Multipath Distance Vector (AOMDV) routing protocol to secure data transmission against blackhole attack in a MANET. ECC, a public key cryptography that works on discrete logarithm problem with a much smaller key size, has been used to encrypt data packets at source node before transmission. We have used AOMDV, a reliable routing protocol compared to its parent protocol, Adhoc On Demand Distance Vector (AODV), with a multipath extension, for routing. The encrypted packets transferring between nodes via AOMDV, has been proved secured against blackhole attack. The performance of the secured protocol has been analyzed in terms of different performance metrics and in terms of varying number of blackhole attacker nodes.